Effectiveness of ice bath therapy after high-intensity exercise in reducing inflammation, oxidative stress, and creatine kinase activity in adolescent males - Adi Pranoto; Irmantara Subagio; Gigih Siantoro; Afif Rusdiawan; Mochamad Purnomo; Donny Ardy Kusuma; Bhekti Lestari; Muhammad Kharis Fajar; I Dewa Made Aryananda Wijaya Kusuma; Bekir Erhan Orhan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Recovery is a vital component of physical activity, serving to restore the body’s physiological equilibrium after intense exertion. However, effective and efficient models of recovery therapy remain underreported in current literature.